Outcomes after tricuspid transcatheter edge-to-edge repair: a systematic review and meta-analysis - Bombace, Sara; Fortuni, Federico; Zancanaro, Edoardo; Luca, Valeria Maria De; Schlotter, Florian; Rommel, Karl-Philipp; Mauro, Michele Di; Squeri, Angelo; Carluccio, Erberto; Condorelli, Gianluigi; Sannino, Anna; Kresoja, Karl-Patrik; et al. (Annals of Cardiothoracic Surgery, 2026)
Background: Severe tricuspid regurgitation (TR) is associated with high morbidity and mortality. Tricuspid transcatheter edge-to-edge repair (T-TEER) improves TR severity and symptoms, yet survival benefit remains uncertain. This meta-analysis aims to evaluate 1-year outcomes after T-TEER and explore clinical and echocardiographic correlates of prognosis. Methods: A systematic search of PubMed/MEDLINE, Web of Science, and Scopus was conducted through June 2025. Studies enrolling ≥100 patients undergoing T-TEER and reporting 1-year outcomes were included. Primary endpoints were 1-year all-cause mortality, heart failure (HF) hospitalization, and persistence of New York Heart Association (NYHA) class III–IV. Early residual TR (≥3+), assessed at the earliest post-procedural time point within 30 days, was a secondary endpoint. Results: Ten studies, including 4,134 patients, were analyzed. At 1-year, pooled all-cause mortality was 14.0% [95% confidence interval (CI): 9.6–18.5%], HF hospitalization 16.9% (95% CI: 8.7–25.1%), and 30.9% of patients remained in NYHA class III–IV (95% CI: 22.1–39.7%). Early residual TR ≥3+ occurred in 19.1%. In meta-regression analysis, more contemporary recruitment periods were associated with lower 1-year mortality, whereas single-center design was associated with higher early residual TR ≥3+. Exploratory aggregate-level analyses suggested potential associations between comorbidity burden and mortality, right-sided dysfunction and HF hospitalization, and left-sided disease and persistent functional limitation. Conclusions: T-TEER effectively reduces TR and improves functional status; however, 1-year mortality and HF hospitalization remain substantial. More contemporary recruitment periods were associated with lower 1-year all-cause mortality, suggesting improved outcomes over time. Systemic comorbidity burden, right-sided disease, and concomitant left-sided disease may contribute to residual risk after T-TEER; however, these associations should be considered hypothesis-generating and require validation in individual patient-level datasets.